Building Children's Creativity Through Short Story Writing Instruction in Elementary Schools - Arina Wulandari (FKIP UNSULTRA, 2025)
Writing short stories is a form of creative expression that can be developed in language learning at the elementary school level. This activity not only enhances language skills but also stimulates children's critical and imaginative thinking abilities. In the context of education, writing short stories provides students with the opportunity to explore ideas, structure narratives, and develop characters and settings in a creative manner. This literature study aims to analyze the role of short story writing in fostering creativity among elementary school students through a literature review method. The analysis results indicate that teaching strategies emphasizing imagination exploration, teacher guidance, and the use of creative media can enhance students’ writing skills and creative thinking. An imagination-based approach allows children to develop ideas freely without rigid constraints, while teacher guidance provides direction and constructive feedback. Additionally, the use of creative media, such as images, music, or digital technology, can serve as inspiration and help children craft richer stories. Beyond improving writing skills, short story writing also contributes to character development and students’ self-confidence. Through the stories they create, children learn to express emotions, understand moral values, and build confidence in presenting their ideas. Therefore, an innovative and interactive approach is necessary for implementing short story writing instruction to maximize its benefits in fostering creativity among elementary school students.